THE INFLUENCE OF FINANCIAL LITERACY AND LOCUS OF CONTROL ON FINANCIAL BEHAVIOR ON STUDENTS OF UNIVERSITAS SANGGA BUANA INSTITUTIONS - Putri, Amelisca Eka; Agusiady, Ricky; Susanto, Bambang; Ratnawati, Aryanti (Multifinance, 2025)
This study aims to examine the effect of financial literacy, locus of control, and lifestyle on the financial behavior of students at Sangga Buana University in Bandung. The background of this study is based on the importance of good financial behavior in supporting financial well-being, especially among students as a productive age group that is forming their financial habits. This study uses a quantitative approach with descriptive and verifiable methods. Data was collected through questionnaires distributed to 100 active student respondents from Sangga Buana University in Bandung. The analysis technique used is multiple linear regression analysis to test the simultaneous and partial effects of the independent variables on the dependent variable. The results showed that simultaneously, financial literacy, locus of control, and lifestyle have a significant effect on students' financial behavior. Partially, financial literacy has a positive and significant effect on financial behavior, which indicates that the higher the students' understanding of finance, the better their financial behavior. Locus of control also has a significant positive effect, indicating that students with confidence in internal control over their lives tend to have better financial behavior. On the other hand, lifestyle has a negative effect on financial behavior, which means that the more consumptive the lifestyle of students, the worse their financial behavior. This study is expected to be a reference for educational institutions in designing programs to improve financial literacy and form positive attitudes toward personal financial management.